Urological Cancer 2021 - López, José I.; Manini, Claudia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Cancer of the urological sphere is a disease continuously increasing in numbers in the statistics of tumor malignancies in Western countries. Although this fact is mainly due to the contemporary increase of life expectancy of the people in these geographic areas, many other factors do contribute as well to this growth. Urological cancer is a complex and varied disease of different organs and mainly affects the male population. In fact, kidney, prostate, and bladder cancer are regularly included in the top-ten list of the most frequent neoplasms in males in most statistics. The female population, however, has also increasingly found itself affected by renal and bladder cancer in the last decade. Considering these altogether, urological cancer is a problem of major concern in developed societies. This Topic Issue of Cancers intends to shed some light into the complexity of this field and will consider all useful and appropriate contributions that scientists and clinicians may provide to improve urological cancer knowledge for patients' benefit. The precise identification of the molecular routes involved, the diagnostic pathological criteria in the grey zones, the dilemma of T1G3 management, and the possible treatment options between superficial, nonmuscle-invasive and muscle-invasive diseases will be particularly welcomed in this Issue.